In Situ Aqueous Spice Extract-Based Antifungal Lock Strategy for Salvage of Foley’s Catheter Biofouled with Candida albicans Biofilm Gel - Bindu Sadanandan; Vaniyamparambath Vijayalakshmi; Kalidas Shetty; Adithya Rathish; Harshala Shivkumar; Malavika Gundreddy; Nikhil Kumar Kagganti Narendra; Nethra Machamada Devaiah (Gels)
Candida forms a gel-like biofilm in the Foley’s catheter (FC) causing tenacious biofouling and severe urinary tract infections (UTIs). For the first time, a spice extract-based antifungal lock therapy (ALT) has been developed to inhibit the Candida albicans gel matrix in FC. Aqueous extracts of garlic, clove, and Indian gooseberry were used as ALT lock solutions and tested against biofilm-forming multidrug-resistant clinical isolates of C. albicans. Reduction in the gel matrices formation in the catheter was confirmed by Point inoculation, MTT assay, CFU, and SEM analysis at 12 and 24 h of incubation. Garlic was effective in controlling both C. albicans M207 and C. albicans S470; however, clove and gooseberry effectively controlled the latter. As evidenced by CFU assay, there were 82.85% and 99.68% reductions in the growth of C. albicans M207 and S470, respectively, at 24 h of incubation. SEM revealed a switch from the biofilm to the yeast mode and a drastic reduction in cell numbers, with mostly clumped or lysed cells. The study will provide an impetus to the development of novel spice extract-based ALT, reducing the selection pressure on the pathogen and lowering antimicrobial resistance. Further research in this area has the potential to leverage clinical applications.